Corporate Governance - Recent Advances and Perspectives 2022
DOI: 10.5772/intechopen.100195
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Corporate Social Responsibility (CSR) Constructs and Theoretical Debate in Pakistan

Abstract: The purpose of this research paper is to review the complete CSR literature laying emphasis on CSR constructs and the theoretical perspectives in Pakistan. Collation of existing empirical and exploratory research has been used to make arguments about current status of academic CSR research. A total of sixty-five published articles on CSR from 2000 to 2021 have been reviewed. A thorough overview of CSR constructs highlighted that overall, the CSR constructs are not properly developed, and theoretical foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…The responsible behavior of businesses toward the stakeholders earns their favor and results in improved financial outcomes (Lopez, 2020; Waheed & Zhang, 2022). Past research has shown a positive relationship between CS and financial performance in Pakistan (Alam & Rashid, 2022). The current study offers a more robust analysis for an extended period between 2011 and 2020 and also controls for the endogenous nature of the CS-corporate financial performance (hereinafter CFP) relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsible behavior of businesses toward the stakeholders earns their favor and results in improved financial outcomes (Lopez, 2020; Waheed & Zhang, 2022). Past research has shown a positive relationship between CS and financial performance in Pakistan (Alam & Rashid, 2022). The current study offers a more robust analysis for an extended period between 2011 and 2020 and also controls for the endogenous nature of the CS-corporate financial performance (hereinafter CFP) relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The lower sustainability reporting in Pakistan is attributed to unstable and weak government structure, unique socio economic and political setup, dependency on foreign aids, lack of education and awareness and weak regulation (Hongming et al, 2020). The research related to CS in Pakistan is deficient in the measurement of the construct and does not consider the theoretical foundations (Alam & Rashid, 2022). The current study adds a new perspective in Pakistan by exploring quality of CS disclosure (monetary/quantitative/statistical/specific) in addition to the level of CS disclosure and builds a comprehensive CS construct.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis then takes a particular focus on scholarship of engagement as the potential exercise of transformative agency where the core business of community engagement and partnerships, of learning and teaching, and of research innovation make for the example of the necessary constructs and discourses for corporate social responsibility constructs. The scholarly engagement of the constructs as discourses, in the contexts of university education and its espoused value for the public and common good, albeit with demonstrable silences about the critical construct of scholarship of engagement, coupled with glaring superficialities as evidenced by the cited crisis events in one case of an institution, allowed for what could be finally declared as the exploratory research whose value was to build on similar studies in other countries [5]. The significance of such exploratory research is thus to advance what ought to be the CSR theorization and conceptualization in social contexts and their expressively veracious considerations.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging economies are facing problems specific to their context and sustainability research should consider the socio-economic realities (Wang et al, 2016). There is meagre research related to sustainability in Asia in general (Ketprapakorn, 2019) and Pakistan is not an exception where the concept is in a nascent stage (Alam & Rashid, 2022). Most of the emerging economies in Asia are suffering from poverty, inequalities, human rights violation, and social exploitations (Belal & Momin, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The study has been designed to collect the corporate sustainability disclosure scores of companies based on content analyses of companies’ documents (Aggarwal & Singh, 2018; Kapoor & Sandhu, 2010: Karim et al, 2020). To date, the construct has not been properly captured in Pakistan (Alam & Rashid, 2022). The study evaluates Pakistani firms and develops a comprehensive corporate sustainability index.…”
Section: Introductionmentioning
confidence: 99%